Impact of light conditions on the early development of Cinchona officinalis. - Vaca-Marquina, S. (2024)
Cinchona officinalis, a native plant species known in Peru as the cinchona tree, has civic importance because it represents the plant wealth of this nation and medicinal importance since it was for more than 300 years the only cure for malaria, and is currently threatened. The aim was to determine the effect of light conditions on the percentage of mortality, height increase, and diameter increase of Cinchona officinalis. In the community of La Cascarilla (5°39'48.87 "S 78°54'35.24 "W), two treatments were installed, forest massif (FM) and enrichment bands (EB). For each treatment, three replicates and 16 plants per replicate were used. Monthly evaluations were carried out in which the number of dead plants, plant height, and diameter were recorded. These parameters were correlated with precipitation, temperature, and photoperiod records of the study area. The results showed that mortality in FM was 27.1% higher than that reported in EB, while the increase in height and diameter increment in the FM plot was 45.5 and 25.1% higher than that obtained in EB. In addition, a negative correlation was observed between the percentage of mortality and precipitation (r s =-0.54), and between the increase in height and diameter increment with the maximum temperature (r s =-0.73 and r s =-0.60, respectively) for the FM treatment, while for the EB treatment, there was a negative correlation between the increase in height and precipitation (r s =-0.55) and a positive correlation between the diameter increment and the minimum temperature (r s =0.53). In general, shaded conditions allow a higher survival rate at the cost of reducing height and diameter increment.